2020
DOI: 10.1016/j.edurev.2019.100309
|View full text |Cite
|
Sign up to set email alerts
|

The impact of in-service professional development on the quality of teacher-child interactions in early education and care: A meta-analysis

Abstract: A growing body of evidence reveals the importance of high-quality teacher-child interactions in early childhood education and care (ECEC) for learning and the behavioral engagement of young children before they enter school (Mashburn et al., 2008;Ponitz, Rimm-Kaufman, Grimm, & Curby, 2009). In general, teachers' performance and effectiveness is seen a function of their behavior in classrooms and their interactions with students. In line with that, the "Teaching Through Interactions" framework (Hamre et al., 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 51 publications
(67 reference statements)
2
34
0
2
Order By: Relevance
“…Previous metanalyses highlighted some characteristics of the training programs that seem to be related to outcomes. Egert et al [17] found that the intensity of CLASS-based trainings (defined as hours spent in group training sessions per month) is negatively associated to ES outcomes. Werner et al [11] found that programs with individual training were more effective than programs without individual training, while program duration and intensity had not been found to moderate program effectiveness.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous metanalyses highlighted some characteristics of the training programs that seem to be related to outcomes. Egert et al [17] found that the intensity of CLASS-based trainings (defined as hours spent in group training sessions per month) is negatively associated to ES outcomes. Werner et al [11] found that programs with individual training were more effective than programs without individual training, while program duration and intensity had not been found to moderate program effectiveness.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…The TTI dimensions have been translated into professional learning and evaluated in several intervention studies to sustain caregiver-child interaction in the early childhood education context [11,16,17]. However, while results from these studies showed improvements in teachers knowledge, skills, and children outcomes, researchers did not reach strong conclusions about the effective elements of caregiver trainings due to heterogeneity in the focus, design, and implementation of these programs [11].…”
Section: Introductionmentioning
confidence: 99%
“…The TSYT is designed to solicit the tutors' instruction, help and guidance, and to speed up young teachers' professional development in their teaching and research. It is a fundamental initiative for faculty development for colleges and a key means for in-service professional training [4].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The development of effective social abilities can be carried out using group or cooperative learning. [11] established that the teaching model can be grouped into 4, including information processing, personal, social, and behavioral groups. All student activities in learning programs have to be democratic, meaning that the learning process should develop the ability as individuals and have a beneficial social ability, which is beneficial for students.…”
Section: Learning Procedures For the Development Of Social Abilitymentioning
confidence: 99%